Book Review: Indigenous Worldview and the Dehypnosis of the West - Lewis (Rafiq), Robert Sean (Journal of the Canadian Association for Curriculum Studies, 2020)
R. Michael Fisher’s Fearless Engagement of Four Arrows: The True Story of an Indigenous-Based Social Transformer recounts the life stories and praxis of Indigenous elder and scholar Four Arrows in order to elucidate how fear management can help us to achieve personal and planetary balance. To this end, the process of subliminal “normalized” fear induction is likened to mass hypnosis, and fear management is understood as a process of dehypnosis whereby we are able to use our entrancement by fear to access intuitive and primal knowledge, thus turning fear into a bridge to personal and planetary transformation. Four Arrows’ systematic approach to fear management is framed in terms of a fear vaccine that he calls CAT-FAWN, which refers to making constructive use of fear-induced “concentration activated transformation” (CAT) by consciously orienting ourselves to the holistic interdependence of “fear, authority, words and nature” (FAWN).